Long and short range order structural analysis of In-situ formed biphasic calcium phosphates. Issue 1 (December 2015) - Kim, Dong-Hyun; Hwang, Kyu-Hong; Lee, Ju; Park, Hong-Chae; Yoon, Seog-Young
Abstract Background Biphasic calcium phosphates (BCP) have attracted considerable attention as a bone graft substitute. In this study, BCP were prepared by aqueous co-precipitation and calcination method. The crystal phases ofin-situ formed BCP consisting of hydroxyapatite (HAp) and β-tricalcium phosphate (β-TCP) were controlled by the degree of calcium deficiency of precursors. The long and short range order structures of biphasic mixtures was investigated using Rietveld refinement technique and high resolution Raman spectroscopy. The refined structural parameters ofin-situ formed BCP confirmed that all the investigated structures have crystallized in the corresponding hexagonal (space group P63/m) and rhombohedral (space group R3c) structures. Results The crystal phases, Ca/P molar ratio, and lattice parameters ofin-situ formed BCP consisting of HAp and β-TCP were controlled by the degree of calcium deficiency of calcium phosphate precursors. The significant short range order structural change of BCP was determined by Raman analysis. Conclusions The long and short range order structural changes ofin-situ formed BCP might be due to the coexistence of β-TCP and HAp crystal phases.